Assessment of bovine biomaterials containing bone morphogenetic proteins bound to absorbable hydroxyapatite in rabbit segmental bone defects - Caporali,Evelyn Hasegawa Gonçalves (2006)
PURPOSE: To evaluate the osteo-regenerative capacity of two proprietary bone grafting materials, using a segmental defect model in both radial diaphyses of rabbits. METHODS: The right defect was filled with pooled bone morphogenetic proteins (pBMPs) bound to absorbable ultrathin powdered hydroxyapatite (HA) mixed with inorganic and demineralized bone matrix and bone-derived collagen, derived from bovine bone (Group A). The left defect was filled with bovine demineralized bone matrix and pBMPs bound to absorbable ultrathin powdered HA (Group B). In both groups, an absorbable membrane of demineralized bovine cortical was used to retain the biomaterials in the bone defects, and to guide the tissue regeneration. The rabbits were euthanized 30, 90 and 150 days after surgery. Radiographic, tomographic and histologic evaluations were carried out on all specimens. RESULTS: At 30 days, the demineralized cortical bone cover was totally resorbed in both groups. HA was totally resorbed from Group A defects, whereas HA persisted in Group B defects. A prominent foreign body reaction was evident with both products, more pronounced in sections from Group B. At 90 days, the defects in Group B exhibited more new bone than Group A. However, at 150 days after surgery, neither treatment had stimulated complete repair of the defect. CONCLUSION: The partial bone healing of the segmental defect occurred with low or none performance of the biomaterials tested.